DETERMINAN PENGUNGKAPAN EMISI KARBON - Aulia Nastiti; Pancawati Hardiningsih (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the factors that influence the disclosure of carbon emissions. The population in this study are mining sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. By using the purposive side technique, the number of samples obtained is 64 companies. The results of this study indicate that size, media exposure, and profitability have a significant positive effect on Disclosure of Carbon Emissions, leverage has an insignificant positive effect on Disclosure of Carbon Emissions, the type of industry has an insignificant negative effect on Disclosure of Carbon Emissions.